Spirituality and religiosity expressed by relatives of drug users: contributions to health care - Camatta,Márcio Wagner (2022)
ABSTRACT Objective: to analyze the expressions of spirituality and religiosity of relatives of people who abuse or are dependent on psychoactive substances. Methods: exploratory-descriptive research that dialogues with the spirituality and religiosity conceptual framework. It was performed at an outpatient clinic specialized in drug treatment in southern Brazil. Semi-structured interviews conducted with 11 relatives of patients undergoing treatment were analyzed by content analysis. Results: the findings were grouped into two categories: forms of expression of spirituality and religiosity practices; and their influence on relatives’ lives. Spirituality and religiosity almost always serve as a protective factor against feelings of anguish, conflicts and loneliness. Final considerations: despite the important role of expressions of spirituality and religiosity for many relatives, not everyone seems to benefit from them. Health professionals should consider these expressions in the construction of comprehensive health care for relatives.